2004
DOI: 10.1088/0953-8984/16/31/026
|View full text |Cite
|
Sign up to set email alerts
|

Optical properties of GaNAs and GaInAsN quantum wells

Abstract: We present an overview of our optical characterization work on dilute nitride quantum well (QW) samples. A simple model for calculating interband transition energies is constructed, tested against published results and used to model experimental data. Steady state photoluminescence (PL), time-resolved PL and photomodulated reflectance measurements are utilized to characterize GaNAs/GaAs, GaInNAs/GaAs and InGaAs/GaAs QWs. The effects of carrier localization, hot-carrier relaxation, non-radiative recombination … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

5
44
0
5

Year Published

2007
2007
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 59 publications
(54 citation statements)
references
References 90 publications
5
44
0
5
Order By: Relevance
“…These values are close to the LO phonon energies of 29 meV in GaInNAs and 36 meV in GaAs. 26 This observation confirms that the transport at temperatures below 120 K is dominated by holes in the QWs, while at T L Ͼ 120 K, it is increasingly dominated by carriers in the barrier layers. In Fig.…”
Section: Methodssupporting
confidence: 70%
See 1 more Smart Citation
“…These values are close to the LO phonon energies of 29 meV in GaInNAs and 36 meV in GaAs. 26 This observation confirms that the transport at temperatures below 120 K is dominated by holes in the QWs, while at T L Ͼ 120 K, it is increasingly dominated by carriers in the barrier layers. In Fig.…”
Section: Methodssupporting
confidence: 70%
“…2͑b͔͒, which is commonly observed at low temperatures in the undoped material. 26 The lack of the S shape is primarily due to the high carrier density in modulation doped QWs screening efficiently the localized exciton transitions. Therefore, the observed behavior can reflect the true temperature dependence of band gap energy and be well fitted by an empirical relation between the band gap and temperature, as proposed by Polimeni et al 27 and Varshni, 28 and previously reported by us.…”
Section: Methodsmentioning
confidence: 99%
“…1(b). The tail is commonly assigned to recombination of localized excitons trapped in potential fluctuations [6,7]. At high temperatures the GaInNAs emission is better represented by two Gaussians, peaks of which are separated by about 35-50 nm, depending on the temperature as showed in Fig.…”
mentioning
confidence: 92%
“…It is clear that the GaInAs emission, which is dominated by free carrier recombination at high temperatures and excitonic recombination at low temperatures, shows no S-shape behaviour but simply follows the expected temperature dependence of the band gap. However, the GaInNAs emission has a strong S-shape behaviour representing temperature-induced transition from L to DL bands (localized to de-localized excitons) as commonly observed in nominally un-doped dilute nitride quantum wells [7][8][9][10]. Initially at temperatures below 90 K peak energy is equal to (E G -E B ) where E G and E B are the band gap and localized exciton binding energy, which might have spread of ∆E B as indicated by the low energy tail of the PL spectra in Fig.…”
mentioning
confidence: 98%
See 1 more Smart Citation